Pengaruh Imbalan dan Lingkungan Kerja Terhadap Kepuasan Kerja (Studi Pada Pegawai Perusahaan Daerah Air Minum Pemerintah Kota Malang) - Warsito, Bambang (Jurnal Ekonomi Modernisasi, 2008)
The Mineral Water Regional Company (PDAM) in Malang is one of the company that was managed by the Government, many sectors have been straightened in order to facing the Regional autonomy. One of these straightens is the human resources sector. Thatâ€™s why the Manager of PDAM must take an interesting in his employee so that they feel satisfied, because the high satisfaction can make the organization more stable, than the purpose of the organization can reach (Dawis, Newstron, 1996, Dharma). The working satisfaction influenced by many factors, repayment is the first factor (Fraza, 1997; Umar, 1999; Mangkunegara, 2000 at Sugiarto, 2000) and the second is working environmental (Siagian, 1995). Now, the Manager of PDAM need to know how is the reaction of the workers to the repayment and the working environmental at PDAM in order to determine the follow up efforts. The result of the hypothesis testing study shows: a) there is a significant influence between materiil repayment variable and non material repayment is a simultant manner to the working satisfaction, with the 67% contribution; b) materiil repayment variable (X1Â) has a significant influence to the working satisfaction (Y) with the 46,6% contribution. Non materiil repayment (X2) has significant influence to the working satisfaction of the workers (Y) with the 31,8% contribution; c) There is a significant influence between lighting variable, ventilation system and the quiet environment in a simultant manner to the working satisfaction of the workers with the 67,90% contribution; d) the lighting variable (X3) has a significant influence to the working satisfaction (Y) with the 32,9% contribution. Ventilation system variable (X4) has a significant influence to the working satisfaction (Y) with the 29,2% contribution. The quiet environment variable (X5) has a significant influence to the working satisfaction (Y) with the 49% contribution; e) there is a significant influence between materiil repayment variable, non materiil repayment, lighting, ventilation system & the quiet environment to the working satisfaction of the workers in a simultant manner with the 77,90% contribution; f) materiil repayment variable (X1) has a significant influence to the working satisfaction (Y) with the 26,2% contribution. Non materiil repayment variable (X2) has a significant influence to the working satisfaction (Y) with the 27,6% contribution. Lighting variable (X3) has a significant influence to the working satisfaction (Y) with the 22,1% contribution. Ventilation system variable (X4) has a significant influence to the working satisfaction (Y) with the 26,4% contribution. Â The quiet environment variable (X5) has a significant influence to the working satisfaction (Y) with the 32,6%